INTERPERSONAL TENSIONS AND PAIN AMONG OLDER ADULTS: THE MEDIATING ROLE OF NEGATIVE MOOD. (16th November 2018) - Graham, J; Huo, M; Birditt, K; Charles, S; Fingerman, K
Abstract: Pain is common in late life and may be exacerbated when older adults incur negative social encounters. Although negative emotion may explain this link, few studies have directly examined this hypothesis. Further, closeness may matter in regard to these associations. This study examined (a) the link between negative social encounters and pain throughout the day, (b) whether the link is mediated by negative emotion, and (c) whether the links vary by closeness with social partners. Older adults (n = 313) completed ecological momentary assessments and reported their social encounters and experiences of pain every 3 hours throughout the day for 5 to 6 days. Multilevel models revealed that negative encounters with any social partner was associated with increased pain at each 3-hour interval. Further, the models revealed evidence of full mediation such that negative social encounters led to pain due to increased negative mood. Additionally, negative encounters with less close social partners were associated with pain; yet, negative encounters with close social partners were not associated with pain. This work suggests that emotion regulation in the context of negative social encounters may be a key factor to improve the daily lives of older adults in pain.